Reinterpreting Models of Slope-Front Recharge in a Desert Basin - Barry J. Hibbs; Mercedes Merino (Geosciences, 2020)
Identification of recharge areas in arid basins is challenging due to spatial and temporal variability and complexity of the hydrogeology. This study re-evaluates recharge mechanism in a desert basin where isotopic and geologic data indicated that published conceptual models of recharge are not accurate. A new model of recharge is formulated that is consistent with the unique geologic framework in the basin. In the area of study, the Rio Grande flows across a broad alluvial floodplain, the “El Paso-Juarez Valley”, where the river has incised the surface of the Hueco Bolson. The modern Rio Grande floodplain overlies the older basin fill, or “Hueco Bolson deposits”, in the valley portion of the area. The lateral contact between the older bolson deposits and the recent alluvial floodplain deposits defines the “slope front”. The valley wall along the slope front is penetrated by many arroyos that incise the Hueco Bolson deposits and modern floodplain surface. The presence of a large lens of freshwater at the boundary between the older bolson fill and recent Rio Grande alluvium seemed to suggest to previous researchers that dilute water developed due to runoff drawn in by San Felipe Arroyo, a prominent arroyo at the slope front between the older Hueco Bolson deposits and the recent Rio Grande alluvium. Our follow-up verification work illustrates that this is demonstrably not the case. The testing of groundwater samples for stable water isotopes and radioisotopes showed that the deeper and more dilute waters near San Felipe Arroyo are actually pre-dam waters recharged from the shifting Rio Grande channel.